170 Maternal Allopurinol Administration During Term Labor is Neuroprotective in Case of Fetal Hypoxia; A Multicenter Randomized Placebo Controlled Trial. (October 2012) - Kaandorp, JJ; Benders, MJNL; Schuit, E; Rademaker, CMA; Oudijk, MA; Porath, MM; Oetomo, S Bambang; Wouters, MGAJ; Elburg, RM van; Franssen, MTM; Bos, AF; Haan, TR de; et al.
Abstract : Background: Hypoxic-ischemic encephalopathy due to perinatal hypoxia-induced free radical formation is an important cause of long-term neurodevelopmental disabilities. Allopurinol reduces the formation of free radicals, which potentially limits hypoxia-induced reperfusion damage. With this trial we aimed to assess whether maternal allopurinol treatment during fetal hypoxia would reduce the release of brain-tissue-specific biomarkers associated with neonatal brain damage. Methods: We performed a randomized double blind placebo controlled multicenter trial (NCT00189007 ) studying laboring women at term with imminent fetal hypoxia. Fetal distress was suspected in case of an abnormal fetal heart rate trace, ST-wave abnormalities on fetal ECG or fetal scalp pH<7.20. Women were allocated to receive allopurinol 500 mg IV or placebo immediately prior to delivery. Endpoints were S100B and neuroketal in cord blood, which are brain-tissue-specific biomarkers for brain damage. Because S100B followed a non-normal distribution, we used a poisson regression model with associated RR (95%CI). For neuroketal we report geometric mean differences. Results: We randomized 222 women to allopurinol (n=111) or placebo (n=111). S100B was significantly lower in the allopurinol-group (median 43.4; IQR 20.2–71.5) compared to the placebo-group (median 54.9; IQR 26.8–94.7), RR 0.91 (95%CI 0.88–0.94). Neuroketal did not significantly differ between groups, geometric mean difference –7.57 (95%CI –15.6; 3.57). Post-hoc analysis showed a marked gender difference in treatment effect in favor of girls for S100B (RR 0.63 (95%CI 0.59–0.68)) and neuroketal (geometric mean difference –16.5 (95%CI –24.6; -1.83)). Conclusion: Maternal treatment with allopurinol during fetal hypoxia reduces damage to neuronal cells as indicated by brain-tissue-specific chemical biomarkers.